Longitudinal Changes in Bone Mineral Density of Healthy Elderly Men in Southern Taiwan - Herng-Chia Chiu (Journal of the Formosan Medical Association, 2008)
Background/Purpose: Longitudinal data on bone decline for Chinese elderly people are sparse, especially for the healthy aged male. We report the longitudinal change in bone mineral density (BMD) at the femoral neck, great trochanter and Ward's triangle in healthy older Taiwanese men. Methods: A prospective cohort study was conducted. We screened 1500 subjects aged ≥ 65 years. One hundred and seventy men were eligible for hip evaluation, and 167 had hip BMD measured. Two years later, 142 men completed follow-up BMD measurement. Linear regression was performed between aging and bone loss. Paired t test was used to determine changes in BMD between the intervals. Results: In the initial study, subjects showed significant bone loss through aging by linear regression at all three sites (p < 0.001). Two years later, there was a significant decrease in BMD at all three sites (p < 0.001). For the age cohort, all the age groups showed a significant decrease in BMD at the three study sites (p < 0.05), except those aged ≥ 75 years at Ward's triangle (p = 0.667) and the great trochanter (p = 0.1). There was a peak loss of BMD in men aged 65–69 years, as high as 5.57% annually at Ward's triangle. Conclusion: BMD was negatively related to aging in healthy men. The loss of BMD in the 65–69 years age group was faster at Ward's triangle than at other sites. Bone loss in Chinese men is of concern because it is greater than in Caucasian men.